AB0125 EXPRESSION OF INTERFERON TYPE I- AND TYPE II-INDUCED GENES IN PATIENTS WITH SJÖGREN’S SYNDROME WITH AND WITHOUT EXTRAGLANDULAR INVOLVEMENT - Del Papa, N.; Vitali, C.; Lorini, M.; Carbonelli, V.; Maglione, W.; Pignataro, F.; Minniti, A.; Montano, N.; Caporali, R. (Annals of the rheumatic diseases, 2020)
Background:It is well known that Sjögren’s syndrome (SjS) is characterized by an upregulation of interferon (IFN)-induced genes. Namely, IFN type I signature has been reported in peripheral blood mononuclear cells (PBMCs) and in salivary glands of patients with this disease. However, few data are available on possible variability of IFN-induced gene upregulation in different clinical phenotypes of SjS.Objectives:To verify whether upregulation of IFN-induced genes is comparable in patients with SjS characterized by different clinical phenotypes, i.e., patients with systemic extraglandular manifestations (EGMs) versus patients with a disease limited to glandular features (GFs) and with widespread pain (WP).Methods:The study population was composed by 11 patients with SjS and EGMs (1 male, age range 18-78 years), and 10 patients with only GFs and WP (all females, age range 46-81 years), all classified according to ACR-EULAR criteria. The prevalence of anti-SSA(Ro) antibodies was 11/11 and 8/10, respectively. Lip biopsy was positive in all cases. Six healthy normal subjects were also included in the study as control population.Four IFN type I- and 5 IFN type II-induced genes were chosen for the study on the basis of previous literature data. Total RNA from each patient and control was isolated from purified PBMCs, followed by cDNA preparation and real time quantitative-PCR (RQ-PCR) analysis, using specific primer/probe sets. For calculation of relative expression, all samples were normalised against expression of a household gene (beta actin). A further normalization was performed against the mean value of relative expression obtained in the normal controls. Final fold change values were determined from the double-normalised values using the 2−ΔΔCT method (Applied Biosystems).Results:Fold change values of gene expression of both IFN type I- and type II-induced genes in PBMCs were different in the two clinical phenotypes of SjS. Fold change values of IFN type I-induced genes appeared strongly higher in patients with EGM, and some of them only moderately increased in those with only GF and WP. The expression of some of IFN type II-induced genes were slightly increased in patients belonging to both clinical phenotypes. Results are detailed in the table.Table.Fold change values of gene expression in patients with SjS plus EGMs, in patients with disease limited to GF and WP, and in controls.GeneMX1IFIT1IFT3IFI44IDO1GRP1MIGIP-10P2RY14SjS-EGMs85.938.524.440.425.18.34.51.55.5SJS-GF-WP4.21.72.04.84.11.20.60.31.3Controls2.11.61.11.51.41.31.51.31.4Legend. IFN type I-induced genes: MIX, IFN-induced GTP binding protein 1; IFIT1, IFN-induced protein with tetratricopeptide repeats 1; IFIT3, IFN-induced protein with tetratricopeptide repeats 3; IFI44, IFN-induced protein 44.IFN type II-induced genes: IDO1, indolamine-deoxygenase 1; GBP1, guanylate binding protein 1; MIG, C-X-C chemokine 9 (CXCL9); IP-10, C-X-C chemokine 10 (CXCL10); P2RY14, purinergic receptor 14.Conclusion:The present data indicate that IFN type I- and, to a lesser degree, type II-induced genes are upregulated in patients with SjS, but this phenomenon is consistently stronger in patients with systemic EGMs. In patients with only GFs IFN-induced gene upregulation is milder in PBMCs, and then probably more restricted to the exocrine target tissues.Disclosure of Interests:Nicoletta Del Papa: None declared, Claudio Vitali: None declared, Maurizio Lorini: None declared, Vincenzo Carbonelli: None declared, Wanda Maglione: None declared, Francesca Pignataro: None declared, Antonina Minniti: None declared, Nicola Montano: None declared, Roberto Caporali Consultant of: AbbVie; Gilead Sciences, Inc.; Lilly; Merck Sharp & Dohme; Celgene; Bristol-Myers Squibb; Pfizer; UCB, Speakers bureau: Abbvie; Bristol-Myers Squibb; Celgene; Lilly; Gilead Sciences, Inc; MSD; Pfizer; Roche; UCB